The impact of increasing health insurance coverage on disparities in mortality: health care reform in Colombia, 1998-2007 (2013)
ABSTRACT: Objectives: We examined the impact of expanding health insurance coverage on socioeconomic disparities in total and cardiovascular disease mortality from 1998 to 2007 in Colombia. Methods: We used Poisson regression to analyze data from mortality registries (633 905 deaths) linked to population census data. We used the relative index of inequality to compare disparities in mortality by education between periods of moderate increase (1998-2002) and accelerated increase (2003-2007) in health insurance coverage. Results: Disparities in mortality by education widened over time. Among men, the relative index of inequality increased from 2.59 (95% confidence interval [CI] = 2.52, 2.67) in 1998-2002 to 3.07 (95% CI = 2.99, 3.15) in 2003-2007, and among women, from 2.86 (95% CI = 2.77, 2.95) to 3.12 (95% CI = 3.03, 3.21), respectively. Disparities increased yearly by 11% in men and 4% in women in 1998-2002, whereas they increased by 1% in men per year and remained stable among women in 2003-2007. Conclusions: Mortality disparities widened significantly less during the period of increased health insurance coverage than the period of no coverage change. Although expanding coverage did not eliminate disparities, it may contribute to curbing future widening of disparities.